2019
DOI: 10.1021/acs.orglett.8b03641
|View full text |Cite
|
Sign up to set email alerts
|

Trideuteromethylation Enabled by a Sulfoxonium Metathesis Reaction

Abstract: A conceptually novel sulfoxonium metathesis reaction between TMSOI and cost-effective DMSO-d 6 is developed for the efficient generation of a new trideuteromethylation reagent TDMSOI. The new reagent TDMSOI is produced highly efficiently by simply heating a mixture of TMSOI and DMSO-d 6 and directly used for subsequent trideuteromethylation in a “one-pot” operation. The preparative power of the new versatile reagent and the “one-pot” protocol is demonstrated by its use to install the −CD3 moiety into broad fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…(entries [13][14][15]. To further improve the yield, several bases were also examined and Et 3 N was found to give the best result (entries [16][17][18]. The investigation of the effect of reaction temperature revealed that 70°C was the optimal temperature (entries [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(entries [13][14][15]. To further improve the yield, several bases were also examined and Et 3 N was found to give the best result (entries [16][17][18]. The investigation of the effect of reaction temperature revealed that 70°C was the optimal temperature (entries [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl sulfoxide (DMSO) is a readily available and less toxic polar solvent [15] . During the past decades, it was reported as important precursors for many organic motifs such as −CH 3 , [16] −CHO, [17] −CN, [18] −SMe, [19] −SOMe, [20] and −SO 2 Me [21] . Cheng's group reported a Cu(I)‐mediated methylthiolation of aryl iodides and aryl bromides with DMSO using ZnF 2 at 150 °C (Scheme 1b) [22] .…”
Section: Introductionmentioning
confidence: 99%
“…This solvent also links to earlier NMR kinetics investigations involving methyl iodide 56 and DMSOmediated methylation studies. 57,58 Importantly, detailed studies applying solvents applicable to a broader range of methylation and catalytic chemistries is also included (see Experimental ESI Sections 20 and 22 †). A graph showing the extent of degradation of each salt aer a 20 min period is shown in Fig.…”
Section: Solid Phase Degradation Analysismentioning
confidence: 99%
“…Very recently, a new trideuteromethylation reagent was developed by a metathesis reaction between [D 6 ]DMSO and trimethylsulfoxonium iodide (TMSOI). [86] This reagent can become a cheap and nontoxic alternative for CD 3 I. The reagent was used as electrophilic CD 3 -reagent (Scheme 21).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%